Estimation of Pelagic Fishing Areas Based on Sea Surface Temperature and Chlorophyll-A Approach in the Maluku Sea - Tangke, Umar (Agrikan Jurnal Agribisnis Perikanan, 2023)
The research was conducted from December 2013 to April 2014 in the Maluku Sea of North Maluku Province with the aim of exploring and mapping pelagic fishing grounds through interviews, statistical analysis and image analysis (GIS) of sea surface temperature and chlorophyll-a distribution. The results showed that the distribution of sea surface temperature during December 2013 to April 2014 was 25.87-30.6 oC, and the distribution of chlorophyll-a concentration during the same month was 0.042-0. 78 mg/m3, the value of these oceanographic factors is still the value preferred by large pelagic fish species and small pelagic fish, while the results of exploration of large and small pelagic fishery resources according to statistical analysis and image analysis of sea surface temperature and chlorophyll-a and interviews with the community show that large pelagic fish species are more influenced by sea surface temperature so that they tend to be in open water while small pelagic fish are more likely to be influenced by chlorophyll-a so that their distribution is more to coastal areas in Maluku Sea waters.